Fiscal federalism, dignity of the human person and public health financing at the Southern Coast of Bahia - Portella, André; Silva, Carine Santos (Saúde e Sociedade, 2023)
This study analyzes the reality of public health financing, focusing on the municipalities of southern Bahia, based on the right to health. To do so, it presents the political and administrative organization of the Brazilian State, understood as a tool for ensuring the effectiveness of fundamental rights, always in line with the principle of human dignity. All the analysis were conducted using empirical data on fund raising and expenditure, mainly referring to the municipalities from the Southern Coast of Bahia.